A theological and missiological study of the role of the miraculous in the doctrinal beliefs and practices of the Church of Pentecost, Ghana - Ayisi-Kumi, Isaac (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.